(untitled) (Bangladesh Journal of Agricultural Research, 2015)
The experiment was conducted at the research field of Regional Agricultural Research Station, Jessore during two consecutive rabi seasons of 2008-2009 and 2009-2010 to find out the effect of hydropriming on the performance of maize seeds under variable soil moisture regimes. The treatments of the experiment were two priming methods viz., i) Hydropriming, ii) Non-priming and four moisture regimes viz., i) Wet condition, ii) Field capacity, iii) 75% of field capacity, and iv) 50% of field capacity. Results showed that yield and yield contributing characters (plant population/m2, number of cobs/m2, length of cob, diameter of cob, 100-grain weight) were influenced significantly by hydropriming. Yield and yield contributing characters were highest when hydroprimed seeds were sown at field capacity whereas it was the lowest at 75% of field capacity from non- primed seeds. Days to tasseling, days to silking, and days to maturity were reduced when hydroprimed seeds were sown at field capacity. At 50% of field capacity, no germination was occurred. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21993 Bangladesh J. Agril. Res. 39(3): 505-513, September 2014